Kinetic Isotope Effect as a Tool To Investigate the Oxygen Reduction Reaction on Pt‐based Electrocatalysts – Part I: High‐loading Pt/C and Pt Extended Surface. Issue 6 (4th February 2020) - George, Thomas Y.; Asset, Tristan; Avid, Arezoo; Atanassov, Plamen; Zenyuk, Iryna V.
Abstract: Kinetic isotope effect (KIE) was used to study the rate‐determining step for oxygen reduction reaction (ORR) on dispersed Pt/C electrocatalyst and polycrystalline Pt (Pt‐poly). KIE is defined as the ratio of the kinetic current measured in protonated electrolyte versus deuterated electrolyte, with KIE values larger than one indicating proton participation in the rate‐determining step. The effect of poisoning anions on the platinum rate determining step is investigated by assessing the KIE in perchloric (non‐poisoning) and sulfuric acid‐based electrolytes. The kinetics currents were calculated using the Koutechy‐Levich and Tafel analysis. A KIE of 1 was observed for Pt/C (with a 40 wt.% Pt loading) and Pt‐poly, thus indicating that, on 40 wt. % Pt/C and Pt‐poly, the rate determining step is proton independent. Abstract : ORR on Pt nanostructures : The ORR rate determining step (r.d.s.) was studied using kinetic isotope effect (KIE) on polycrystalline Pt and Pt nanoparticles densely packed on a carbon support. The KIE consists of comparing the kinetics in a proton‐ and a deuteron‐based electrolyte. The results showed that, for both Pt nanostructures, the r.d.s. was proton independent, therefore consisting of an electron transfer.